An analysis of a benchmarking initiative to help government entities to learn from best practices – the "Dubai We Learn" initiative. Issue 1 (19th May 2020) - Mann, Robin; Adebanjo, Dotun; Abbas, Ahmed; El Kahlout, Zeyad Mohammad; Al Nuseirat, Ahmad Abdullah; Al Neaimi, Hazza Khalfan
Abstract : Purpose: This paper aims to investigate the mechanisms for managing coordinated benchmarking projects and the outcomes achieved from such coordination. While there have been many independent benchmarking studies comparing the practices and performance of public sector organisations, there has been little research on initiatives that involve coordinating multiple benchmarking projects within public sector organisations or report on the practices implemented and results from benchmarking projects. This research will be of interest to centralised authorities wishing to encourage and assist multiple organisations in undertaking benchmarking projects. Design/methodology/approach: The study adopts a case study methodology. Data were collected on the coordinating mechanisms and the experiences of the individual organisations over a one-year period. Findings: The findings show successful results (financial and non-financial) across all 13 benchmarking projects, thus indicating the success of a coordinated approach to managing multiple projects. The study concluded by recommending a six-stage process for coordinating multiple benchmarking projects. Originality/value: This research gives new insights into the application and benefits from benchmarking because of the open access the research team had to the "Dubai We Learn" initiative. To the authors' knowledge the research was unique in being able to report accurately on the outcome of 13 benchmarking projects with all projects using the TRADE benchmarking methodology.